The fall of the Templar - Benz, Derek; Lewis, J. S. (Jon S.) (New York, NY : Orchard Books, 2008)
Eleven-year-old Max Sumner and the Grey Griffins continue to be tested and trained while the Black Wolves, commanded by Max's own father, and Morgan La Fey use the Spear of Ragnarok in their attempt to destroy the world.
850
Accelerated Reader AR
Keywords: Magic -- Fiction; Animals, Mythical -- Fiction; Fairies -- Fiction; Monsters -- Fiction; Children's stories